Randomized feasibility trial of replacing or discarding the nail plate after nail-bed repair in children. Issue 12 (17th October 2017) - Greig, A; Gardiner, M D; Sierakowski, A; Zweifel, C J; Pinder, R M; Furniss, D; Cook, J A; Beard, D; Farrar, N; Cooper, C D; Jain, A; Agha, R; et al.
Abstract: Background: Nail-bed injuries are the most common hand injury in children. Surgical dogma is to replace the nail plate after repairing the nail bed. Recent evidence suggests this might increase infection rates and returns to clinic. The aim of this feasibility trial was to inform the design and conduct of a definitive trial comparing replacing or discarding the nail plate after nail-bed repair. Methods: This study recruited participants from four hand units in the UK between April and July 2015. Participants were children under the age of 16 years with a nail-bed injury requiring surgery. They were randomized to either having the nail plate replaced or discarded after nail-bed repair. The follow-up method was also allocated randomly (postal versus clinic). Information was collected on complications at 2 weeks and 30 days, and on nail-plate appearance at 4 months using the Zook classification. Two possible approaches to follow-up were also piloted and compared. Results: During the recruitment phase, there were 156 potentially eligible children. Sixty were randomized in just over 3 months using remote web-based allocation. By 2 weeks, there were two infections, both in children with replaced nail plates. The nail-replaced group also experienced more complications. There was no evidence of a difference in return rates between postal and clinic follow-up. Conclusion: Recruitment was rapid and nail-bed repair appeared to have low complication and infection rates in this pilot trial. The findings have led to revision of the definitive trial protocol, including the mode and timing of follow-up, and modification of the Zook classification. Abstract : Informs the RCT